Static and Dynamic Response of Ultra-Fast Annealed Advanced High Strength Steels - Castro-Cerda, F (EDP Sciences, 2018)
Ultra-fast annealing (UFA) is a viable alternative for processing of 3rd generation advanced high strength steels (AHSS). Use of heating rates up to 1000°C/s shows a significant grain refinement effect in low carbon steel (0.1 wt.%), and creates multiphase structures containing ferrite, martensite, bainite and retained austenite. This mixture of structural constituents is attributed to carbon gradients in the steel due to limited diffusional time during UFA treatment. Quasi-static (strain rate of 0.0033s-1) and dynamic (stain rate 600s-1) tensile tests showed that tensile strength of both conventional and UFA sample increases at high strain rates, whereas the elongation at fracture decreases. The ultrafast heated samples are less sensitive to deterioration of elongation at high strain rates then the conventionally heat treated ones. Based on metallographic studies was concluded that the presence of up to 5% of retained austenite together with a lower carbon martensite/bainite fraction are the main reason for the improved tensile properties. An extended stability of retained austenite towards higher strain values was observed in the high strain rate tests which is attributed to adiabatic heating. The extension of the transformation induced plasticity (TRIP) effect towards higher strain values allowed the UFA-samples to better preserve their deformation capacity resulting in expected better crashworthiness. © 2018 The Authors, published by EDP Sciences.